Zadania edukacji w kontekście refleksji nad tożsamością narodową uczniów szkół polskich w Wilnie .......... 105 (Tożsamość na styku kultur: 4, 2021)
EDUCATIONAL TASKS IN THE CONTEXT OF THE REFLECTION ABOUT THE NATIONAL IDENTITY OF POLISH SCHOOL STUDENTS IN VILNIUSThe aim of the article is to describe the complex national identity of Polish students in Vilnius and on this basis, to outline the most important tasks of Polish language education in Lithuania. Based on the conducted research and referring to the sociological theory of the non-uniform understanding of the nation in ethnic, political and cultural terms, the author describes the identity of students in the three dimensions mentioned. Research has shown that in the conditions of multiculturalism, the civic, ethnic, and cultural identity of schoolchildren is a complex system of interrelated but distinct values. The description of this phenomenon leads to a discussion of the most urgent tasks of the Polish school in Lithuania.